Performance Analysis of Two-Way AF Relaying Systems Over Cascaded Nakagami-m Fading Channels - Ilhan, Haci (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
In this letter, we investigate the error rate performance of two-way amplify-and-forward (AF) relaying communication system over independently but not necessarily identically distributed (i.n.i.d.) cascaded Nakagami-m fading channels. We have derived a closed-form expressions of cumulative distribution function (CDF) and moment generating function (MGF) for considering system. By using these expressions, we analyse the performance of two-way AF relaying system in terms of outage probability and symbol error rate (SER). Numerical and simulation results show the validity of the proposed mathematical analysis and point out the confirmation of the analytical results.
Keywords: Cascaded Nakagami-m fading channels; cumulative distribution function; moment generating function; outage probability; symbol error rate performance; two-way amplify-and-forward relaying; EFFICIENT PROTOCOLS; RAYLEIGH; TRANSMISSION; DIVERSITY; CODES; Engineering